2020
DOI: 10.1016/j.jaim.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Improved drug carriage and protective potential against Cisplatin-induced toxicity using Boldine-loaded PLGA nanoparticles

Abstract: Compared to Boldine (Bol), NBol had better ability of drug carriage and protective potentials (29.00% approximately) against Cisplatin-induced toxicity. Combinational therapeutic use of PLGA-NBol can reduce unwanted Cisplatin-induced cellular toxicity facilitating use of Cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Recent studies have focused on the use of poly(lactide- co -glycolic) acid as a material for the synthesis of nanoparticles to encapsulate therapeutic agents for the treatment of Alzheimer’s disease [42] and brain cancer [43,44]. In vitro studies showed that the use of polymeric nanoparticles enhanced drug delivery to the brain, with reduced oxidative stress, inflammation and plaque load through the improved delivery of curcumin for treating Alzheimer’s disease [42], and efficient internalization of doxorubicin into the human glioma cells, resulting in cytotoxic effect on cancer cells [43].…”
Section: Nanotechnology Approaches For Crossing the Blood-brain Bamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have focused on the use of poly(lactide- co -glycolic) acid as a material for the synthesis of nanoparticles to encapsulate therapeutic agents for the treatment of Alzheimer’s disease [42] and brain cancer [43,44]. In vitro studies showed that the use of polymeric nanoparticles enhanced drug delivery to the brain, with reduced oxidative stress, inflammation and plaque load through the improved delivery of curcumin for treating Alzheimer’s disease [42], and efficient internalization of doxorubicin into the human glioma cells, resulting in cytotoxic effect on cancer cells [43].…”
Section: Nanotechnology Approaches For Crossing the Blood-brain Bamentioning
confidence: 99%
“…In vitro studies showed that the use of polymeric nanoparticles enhanced drug delivery to the brain, with reduced oxidative stress, inflammation and plaque load through the improved delivery of curcumin for treating Alzheimer’s disease [42], and efficient internalization of doxorubicin into the human glioma cells, resulting in cytotoxic effect on cancer cells [43]. Additionally, the in vivo experiment regarding the co-delivery of cisplatin and boldine, an antioxidant agent, using the poly(lactide- co -glycolic) nanocarriers resulted in an effective target-specific delivery for therapeutic use in brain cancer therapy [44]. Furthermore, the use of a positively charged polymer, poly(ethylene imine) [45], and of the poly(ethylene imine)-poly( l -lysine) copolymer [46] as gene delivery vehicles has been reported.…”
Section: Nanotechnology Approaches For Crossing the Blood-brain Bamentioning
confidence: 99%
“…Studies regarding the treatment of brain cancer focused on the delivery of various anti-cancer drugs using nanocarriers. Specifically, poly(lactide- co -glycolic) acid nanoparticles containing doxorubicin, cisplatin, and boldine resulted in an efficient internalization into the glioma cells, inducing cytotoxic effects [86] and an effective target-specific delivery [87]. Other polymeric nanocarriers for the treatment of brain cancer include polyethylene glycol and poly(ω-pentadecalactone- co - p -dioxanone) [88] or polyethylene glycol and poly(lactic- co -glycolic) acid [89] block copolymer nanoparticles which led to an improved drug release efficiency and a decrease in tumor size.…”
Section: Nanomedicine In Central Nervous System Disordersmentioning
confidence: 99%
“…The ease of PLGA nanoparticle functionalization, and biodegradability are the major features that make it a suitable candidate for drug delivery. (5,6) Coating of blood brain targeting nanoparticles with a surfactant such as polysorbate 80 is one of the strategies to deliver drug molecules to brain in a more effective way. 7The polysorbate 80 coating enables receptor-mediated endocytosis across the blood-brain barrier by adsorbing to plasma proteins such as apolipoprotein E. The method proved far more efficient as drug delivery system compared to the free drug used.…”
Section: Introductionmentioning
confidence: 99%